2013
DOI: 10.1016/j.str.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Giant Ca2+-Binding Adhesin SiiE: Implications for the Adhesion of Salmonella enterica to Polarized Epithelial Cells

Abstract: SiiE from Salmonella enterica is a giant 5,559-residue-long nonfimbrial adhesin that is secreted by a type 1 secretion system (T1SS) and initiates bacterial adhesion to polarized host cells. Structural insight has been gained into the 53 bacterial Ig-like (BIg) domains of SiiE, which account for 94% of the entire SiiE sequence. The crystal structure of a fragment comprising BIg domains 50 to 52 of SiiE reveals the BIg domain architecture and highlights two types of SiiE-specific Ca²⁺-binding sites. Sequence ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 43 publications
2
65
0
Order By: Relevance
“…A Phyre 2 model (Fig. 1A) (51) predicts that the structure of these repeats is similar to that of the bacterial immunoglobulin-like domain group 3 (BIg 3) repeats found in the Salmonella enterica nonfimbrial adhesin SiiE (57). Like other RTX nonfimbrial adhesins (47), TosA also contains 10 RTX repeats near its carboxyl terminus (27) and a putative transmembrane domain near its amino terminus.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…A Phyre 2 model (Fig. 1A) (51) predicts that the structure of these repeats is similar to that of the bacterial immunoglobulin-like domain group 3 (BIg 3) repeats found in the Salmonella enterica nonfimbrial adhesin SiiE (57). Like other RTX nonfimbrial adhesins (47), TosA also contains 10 RTX repeats near its carboxyl terminus (27) and a putative transmembrane domain near its amino terminus.…”
Section: Resultsmentioning
confidence: 71%
“…These immunoglobulin folds mediate protein ligand interactions, which endow SiiE with adhesive properties (65). In addition, these immunoglobulin folds, coupled with Ca 2ϩ binding, could also promote SiiE length extension (57), bringing it into proximity with its cognate receptor on the host cell. However, whether the BIg 3 repeats found in TosA mediate adherence, extend TosA such that an element in the carboxyl terminus can mediate adherence, or some combination of these two is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although low sequence identity (< 20%) is shared between the repetitive domains of these adhesins and MpAFP_RII, bioinformatics analyses have indicated that they are also tandem BIg modules. Indeed, the recently solved structure of such segments from the epithelial adhesin SiiE (Salmonella enterica) showed three tandem BIg domains with their intervening loop regions rigidified by Ca 2+ coordination [37]. The authors proposed that the Ca 2+ -induced region of BIg repeats can help SiiE reach out beyond the Salmonella lipopolysaccharide layer, which is key to promoting the adhesion to host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these proteins contain glycine-rich repeats that bind calcium ions. For example, the SiiE protein of Salmonella enterica is 5,559 amino acids long and contains 53 BIg3_4 domains in addition to the T1SS recognition domain22. The SiiE protein has been shown to interact with more than 100 calcium ions and to mediate adhesion to polarized epithelial cells23.…”
Section: Resultsmentioning
confidence: 99%